Memória autobiográfica e eventos estressores traumáticos - Lorenzzoni, Pânila Longhi (2013)
This dissertation is composed of two studies, one systematic review and one empirical study, presented in the form of articles. The overall objective of the study was to investigate alterations in Autobiographical Memory (AM) in people with and without Posttraumatic Stress Disorder (PTSD) in comparison to people who never experienced traumatic situations. The systematic review paper aimed to discuss about the alterations in AM components in different groups of people (with and without PTSD, no trauma). Empirical article is characterized as a cross-sectional survey of contrasting groups and aimed to investigate whether changes in AM are exclusively to PTSD or are also observed in subjects who have suffered trauma and did not develop PTSD. Therefore, research was conducted overall memory in order to investigate whether the alterations observed in AM do not suffered influences from other functional alteration in memory. It was found that there are significant differences among the three study groups, especially in centrality, identity and overgeneralization. The Trauma + PTSD Group showed more significant changes compared to the AM Trauma Group and the Control Group, suggesting that the AM alterations are related to posttraumatic symptoms intensity.